Assessment of the diagnostic value of specific anti-Toxocara IgA in Slovakian patients suspected to have toxocarosis - Boldiš, Vojtech; Ondriska, František; Lipková, Simona (Folia microbiologica, 2018)
Human toxocarosis is one of the most widespread and prevalent helminthic zoonosis in many countries, including Slovakia. The aim was to evaluate the usefulness of IgA anti-Toxocara antibody detection in the serodiagnosis of toxocarosis. The levels of specific IgA antibodies were determined by excretory-secretory (ES)-enzyme-linked immunosorbent assay (ELISA). The IgA seropositivity in IgG anti-Toxocara seropositive patients (n = 52) was 32.7% and found to be highest in the oldest age groups (P = 0.026). The presence of IgA in suspected patients for toxocarosis were evaluated in respect to some characteristics of examined persons. Substantially higher IgA seropositivity was detected in patients with increased total IgE (44.8%) than in subjects with a normal level of IgE (17.4%; P = 0.036). No associations (P > 0.05) were found between IgA seropositivity and sex, level of specific IgG antibodies, avidity of IgG, eosinophilia, domicile, geophagia, traveling abroad, dog/cat ownership, or clinical symptoms. The IgA-ELISA showed sensitivity of 57.1% and specificity of 100%. Mild correlations (r = 0.302, r = 0.305, r = - 0.409) were observed between the levels of anti-Toxocara IgA antibodies and age, the amounts of eosinophils and IgA antibody levels, the amounts of eosinophils, and the values of IgG avidity, respectively. The presence of anti-Toxocara IgA may facilitate the diagnosis of toxocarosis and may well be useful for the determination of acute Toxocara infection. Moreover, this test should be accompanied by other immunological markers of examined patients (e.g., increased total IgE, eosinophilia, and low-avidity IgG antibodies).
Keywords: Antibodies, Helminth; dospělí; Animals; Serum Bactericidal Antibody Assay; Female; Infant; dítě; předškolní dítě; Age Factors; Toxocariasis; Adult; ženské pohlaví; mladý dospělý; Adolescent; Slovakia; věkové faktory; lidé; protilátky helmintové; Sensitivity and Specificity; Immunoglobulin E; protilátky anti-idiotypické; Aged, 80 and over; senzitivita a specificita; Male; kojenec; Aged; Child, Preschool; Young Adult; test sérových baktericidních protilátek; toxokaróza; imunoglobulin E; lidé středního věku; Child; senioři nad 80 let; Slovenská republika; senioři; zvířata; mužské pohlaví; Toxocara; Antibodies, Anti-Idiotypic; Middle Aged; mladiství; Humans